Genetic Diversity of South Chadian Sorghum Landraces Assessed Through Quantitative and Qualitative Traits - Naoura, Gapili; Hassane, Mahamat Alhabib; Reoungal, Djinodji; Signaboubo, Serferbe; Rattunde, Eva Weltzien- (International Journal of Applied Sciences and Biotechnology, 2019)
Plant genetic resources and germplasm are fundamental sources for plant breeding, and the assessment of the genetic diversity among germplasm accessions is useful to facilitate the more efficient use of plant genetic resources. The current study was carried out to estimate genetic variability, heritability and genetic advance to select genotypes and traits for breeding. In the experiment undertaken, fifty-three sorghum landraces were evaluated for selected seven qualitative and fourteen quantitative traits using randomized complete block design in three repetitions. There were differences (p< 0.001) among landraces for all assessed traits indicating a high degree of variability. Higher genotypic coefficient of variation and phenotypic coefficient of variation were observed for grain weight of main panicle, number of leaf remain green and weight of main panicle. Estimates of phenotypic variances were higher than genotypic variance for all the studied quantitative traits. High heritability coupled with high genetic advance as per cent of mean was observed for majority of assessed traits. This study allowed noting a positive relationship between number of day to flowering with plant height and stay green, and a negative correlation between plant height and weight of main panicle. A dendrogram revealed four main clusters of genotypes. The D2 statistics confirmed the highest inter-cluster distance between all clusters. This indicated existence of the possibility to improve genotypes through hybridization from any pair of clusters.